AKTIVITAS KANDUNGAN DAUN SIRIH (Piper betle L.) SEBAGAI ANTIOKSIDAN : LITERATURE REVIEW ARTICLE - Himyatul Hidayah; Farhamzah; Surya Amal; Iis Dahlia (Jurnal Buana Farma, 2022)
Antioxidants are compounds that can inhibit the oxidation of lipids or other molecules by inhibiting the initiation or propagation of chain oxidation reactions. Exogenous antioxidants consist of natural antioxidants and synthetic antioxidants. Concerns about the side effects of using synthetic antioxidants that can increase carcinogenesis have encouraged the use of natural antioxidants as an alternative source of antioxidants. One source of natural antioxidants can be obtained from plant species that contain antioxidants, namely those from Piper betle L. This literature review article aims to determine the content of Piper betle L. betel leaf as an antioxidant. The literature search process used is Google Scholar, PubMet and Science Direct published in 2011-2021. And the search results found 12 articles with each article stating that Piper betle L. Has antioxidant activity which is included in the category of very strong IC50 values. This is because betel contains quercetin, phenolic compounds, chlorogenic acid, atoxin, eugenol and gallic acid